2017
DOI: 10.1513/annalsats.201609-673oc
|View full text |Cite
|
Sign up to set email alerts
|

Dose De-escalation of Intrapleural Tissue Plasminogen Activator Therapy for Pleural Infection. The Alteplase Dose Assessment for Pleural Infection Therapy Project

Abstract: There may be differences between this version and the published version. You are advised to consult the publisher's version if you wish to cite from it.http://eprints.gla.ac.uk/154169/ Conflict of Interests:YCGL is a member of the advisory board for Lung Therapeutics Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 23 publications
4
66
1
Order By: Relevance
“…This regime is yet to be tested in larger RCT’s. Despite a similar bleeding incidence, of approximately 6%, such a regime may help alleviate some of the anxiety surrounding the use of IPFT as well as making it more cost‐effective. A small prospective observational study of 38 patients looked to simplify the regime comparing concurrent vs. sequential intrapleural instillation of tPA and DNase, removing the 1 hr interval between each administration, and reported similar treatment success .…”
Section: Treatmentmentioning
confidence: 99%
“…This regime is yet to be tested in larger RCT’s. Despite a similar bleeding incidence, of approximately 6%, such a regime may help alleviate some of the anxiety surrounding the use of IPFT as well as making it more cost‐effective. A small prospective observational study of 38 patients looked to simplify the regime comparing concurrent vs. sequential intrapleural instillation of tPA and DNase, removing the 1 hr interval between each administration, and reported similar treatment success .…”
Section: Treatmentmentioning
confidence: 99%
“…Heterogeneity is therefore common in clinical practice. Interestingly, there is increasing evidence to support the use of lower doses of tPA (with deoxyribonuclease (DNase)) as intrapleural therapy for pleural infections . A prior case report has described the successful use of tPA doses as low as 1 mg, together with 5 mg DNase, in the setting of pleural infection in a patient with high bleeding risks .…”
Section: Discussionmentioning
confidence: 99%
“…The bleeding risk and costs associated with tPA remain clinicians’ major concerns. Recent dose de‐escalation studies found a similar success rate using 5 mg of tPA and further studies using 2.5 mg are underway .…”
Section: Introductionmentioning
confidence: 89%